Ectopic Thyroid Papillary Carcinoma with Cervical Lymph Node Metastasis as the Initial Presentation, Accompanied by Benign Thyroid Gland - Kola, Erisa; Ylli, Agron; Nakuci, Daniela; Dervishi, Migena; Musa, Juna; Horjeti, Edlira; Gjergji, Dashamir; Alimehmeti, Mehdi (Medical archives (Sarajevo, Bosnia and Herzegovina), 2021)
Ectopic thyroid papillary carcinoma presenting as bilateral neck lymph nodes metastasis is very rare. Ectopic thyroid tissue may appear in any location along the trajectory of the thyroglossal duct from the foramen cecum to the mediastinum. It is subject to malignant transformation and is classically accompanied by a similar transformation of the native thyroid gland. Similar to that of the native thyroid gland, the most common malignancy found is Papillary thyroid carcinoma. Unusual cases in which ectopic thyroid carcinoma presents with normal native tissue support an alternative hypothesis that ectopic thyroid tissue may develop malignancies independently from the native thyroid gland. We present an extremely rare case of a 30-year-old woman previously diagnosed with Hashimoto's thyroiditis, presenting with a palpable mass in the lateral neck suspicious for malignancy. After several examinations and surgical removal of the mass, histopathologic evaluation of the continuous sections of the thyroid, demonstrated metastatic disease from papillary carcinoma of the thyroid. Total thyroidectomy and biopsy revealed benign thyroid tissue without any foci of microcarcinoma. A hypothesis of ectopic thyroid tissue and its malignant transformation was made. By presenting this case, our goal is to highlight and make the physicians aware of the possibility of developing primary carcinoma of the ectopic thyroid tissue, without an active tumor of the thyroid gland.